Optimalisasi Aksesibilitas Jalur Pejalan Kaki Bagi Penyandang Disabilitas (Studi Kasus Jalan Blora dan Jalan Kendal Dukuh Atas) - Nugraha, Adam; Budi Purnomo, Agus; Budi H, Nurhikmah (Jurnal Etnik: Ekonomi-Teknik, 2023)
Public service is a form of service provided by the service manager, in this case the DKI Jakarta City Government. The government needs to ensure that these services are distributed fairly and equally to meet the needs of all members of society, without exception. One type of public service that must be provided to the community is accessibility services. Accessibility can be obtained through physical access, such as pedestrian paths (sidewalks) for persons with disabilities. In 2019, there were 14,459 individuals with disabilities in DKI Jakarta. Even though the level of mobility in the area is high, it is important to ensure that all residents have adequate accessibility to public facilities. By providing physical infrastructure that is friendly to persons with disabilities, their capabilities can be increased. This study aims to evaluate how Regional Regulation No. 10 of 2011 fulfills the accessibility of public facilities for persons with disabilities in DKI Jakarta. This study is a descriptive case study using a qualitative approach. A survey technique of academic literature in the field of public services is used to find concepts that are relevant to the accessibility of public roads (pedestrian paths) for persons with disabilities. Data was collected by tracing sources and literature from government documents, electronic mass media, journals and books related to this research. In addition, documentation techniques in the field such as taking photos and observations are also used to strengthen the data.